Case series of patients with early psychosis presenting hypoperfusion in angular gyrus and self‐disturbance: Implication for the sense of agency and schizophrenia - Akane Yoshikawa; Youhei Obata; Chihiro Kakiuchi; Atsushi Nakanishi; Satoshi Kimura; Shigeki Aoki; Tadafumi Kato (Wiley, 2024)
Abstract Background Self‐disturbance has been considered as a core symptomatology of schizophrenia and its emergence from the prodromal phase makes it a crucial target for early detection and intervention in schizophrenia. Currently, the clinical assessment of self‐disturbance relies on the self‐report of patients, and clinicians have no diagnostic tools in clinical practice. Identifying the neural substrate of self‐disturbance would be of great clinical value by shedding light on the core dimension of schizophrenia. Case Presentation We first introduce an adolescent patient who initially presented self‐disturbance, and clinically detectable hypoperfusion in angular gyrus (AG) was observed when early psychosis was suspected. Interestingly, the hypoperfusion in AG may correspond to improvement and exacerbation of self‐disturbance. This clinical observation led us to pursue the relationship between the decreased blood flow in the AG and self‐disturbance. Among 15 cases with suspected early psychosis in which single photon emission computed tomography was performed to exclude organic factors, we found additional 5 cases, including one prodromal patient, showing hypoperfusion in the AG and self‐disturbance with significant correlation (r = 0.79, p = 0.00025). Discussion The self‐disturbance has been interpreted as a reflection of disturbance of the "Sense of Agency", the ability to attribute their action and/or thoughts to themselves. AG has been shown to play a pivotal role in the sense of agency. These cases suggest that the hypoperfusion in AG associated with the disruption in the sense of agency would be an early clinical sign of schizophrenia. Further longitudinal studies are needed to test this hypothesis.